(untitled) (Innovative professional education, 2025)
The article investigates the effectiveness of using digital platforms in the professional training of qualified workers in the «Motor Transport» industry. Based on the results of an experiment conducted at the Regional Center for Vocational Education named after O.S. Yegorov, the impact of digital tools on the quality and effectiveness of vocational education is assessed, in particular for the profession of «Wheel Vehicle Repair Mechanic». The results of the study emphasize the advantages of integrating digital platforms into curricula, including access to educational materials, the possibility of a personalized approach to learning, and improving the acquisition of practical skills and competencies.